Study on rural development in Barbados - Instituto Interamericano de Cooperación para la Agricultura (IICA) (Instituto Interamericano de Cooperación para la Agricultura (IICA), 2020)
This study, carried out in collaboration with the Ministry of Agriculture, Food and Fisheries, responds to the need for understanding rural development experiences in Barbados. It examines the history of rural development and identifies and describes major projects, participants and their contributions. It also identifies project ideas and actions to guide the formulation of a rural development strategy for Barbados research for this document began with a meeting of rural development specialists from the public and private sectors to identify available information, major projects and key participants, and to discuss strategies and options for future development.